Ḵẖairulifādat : yaʻnī, Malfūẓāt-i ̤tayyibāt - Thānvī, Ashraf ʻAlī (Idārah-yi Islāmiyāt ; Milne ke pate, Dārulishāʻat, 1982)
Teachings of a Muslim religious scholar of the Deoband School of Islamic thought.